Digitalisasi Sistem Akuntansi pada UMKM: Tinjauan Literatur tentang Faktor Penghambat dan Pendorong Keberhasilan Pelaporan Keuangan - Siti Khaeryyah (Journal of Innovative and Creativity, 2026)
The digitalization of Accounting Information Systems (AIS) is an absolute prerequisite for the sustainability of Micro, Small, and Medium Enterprises (MSMEs) in the digital economy era. However, a disconnect persists between the availability of technology and its practical implementation, resulting in low-quality financial reporting and barriers to accessing financing. This study aims to synthesize recent literature to identify critical factors determining the success of accounting digitalization in MSMEs. Employing a Systematic Literature Review (SLR) method, this research maps trends over the past five years and classifies driving and inhibiting factors from technological, organizational, and environmental perspectives. The synthesis integrates the Technology–Organization–Environment (TOE) framework and the Technology Acceptance Model (TAM) to provide a holistic understanding of technology adoption dynamics. This study is expected to contribute theoretically to the development of technology adoption models and practically to assist regulators in designing a more adaptive digital accounting ecosystem for MSMEs.